THE FACTORS AFFECT CONSUMER PURCHASING BEHAVIOR OF VIETNAMESE BRANDED COFFEE PRODUCTS IN HANOI CITY - Pham, Thu Hien (Khoa Quốc tế, ĐHQGHN, 2019)
Strongly development of the coffee industry shows vital role of this beverage in the our daily life. Vietnam is in the top five Asian countries for coffee consumption per capita after Japan, South Korea and Thailand. With population of over 90 million people, it has a difference in the coffee culture that older than in other countries. This is a lucrative market for Vietnamese coffee companies to exploit and develop their brands. But the reality shows that this potential market is to be omitted because Vietnamese coffee enterprises focus on exporting green coffee. In a current market economy, the fierce competition occurs among businesses and anyone who wants their products or services to be attended and selected by customers. In order to achieve that goal, it is not only base on factors such as good quality products, competitive price, also on other elements that need to be resolved for instance what customers need and want, how their demand change, buying motivation and the personality traits of each customer group as well as the factors directly and indirectly impact on their buying behavior, etc. For a long-term, stable development, enterprises need to understand the psychology, age, occupation, average income, behavior of their customers.